Manual of poultry production in the tropics - Say, Ralph R., tran. (CAB International OxonGB, 1987)
Discusses a variety of topics including anatomy and physiology of poultry; breeds and strains; poultry feeding; diseases; poultry farm management; merchandising of poultry products; economics of poultry farming and the rearing of guinea fowl and ducks.